USING GROUP DISCUSSION TO IMPROVE STUDENTS’ SPEAKING FLUENCY - Ibnu Wahyurianto (Journal of English for Academic and Specific Purposes)
Being able to speak in target language is considered as the indicator that every language learner is mastering the target language. Likewise in English, the learners are regarded mastering English when they can produce the sound of English itself in the form of good communication toward the others. Nevertheless, teaching English is a complex process, since it involves some activities started from preparation until evaluation. In addition, there are some barriers regarding teaching speaking, i.e the number of students, teacher’s competence, and even students’ problems. Although teaching speaking is a kind of difficult job, still there is a way to overcome some stated problems; group discussion. So, this research is aiming at the implementation of group discussion to improve students’ speaking fluency. To achieve the research objectives, the design of the research is classroom action research which involves four steps, they are planning, implementing, observing, and reflecting. The subject research is the students of Bahasa Indonesia Department semester II of University of Muhammadiyah Malang who have different English proficiency background. Data collection method used is preliminary observation, indepth interviews, participatory observation, and documentation. The data gathered will be analyzed by using the qualitative analysis involving reducing data, displaying data, verifying data and taking conclusion. Based on the results, it can be stated that the implementation of group discussion in speaking course can improve the students’ speaking fluency.